Geometric Modeling of River Estuary to Support Normalization Program of Veteran River, Banjarmasin City - Ferry Sobatnu; Nurul Inayah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The city of Banjarmasin is in fact included in the tidal water zone. The Veteran River is one of the canals made by the Dutch to prevent flooding. This research applies geomatics and survey technology to show actual conditions at the mouth of the Veteran River by modeling geometric shapes, using terrestrial and bathymetric measurement data and corrected Pleiades satellite imagery. Modeling using the Gridding method can create geometric shapes of land surface appearances in 3 dimensions. The modeling results show that the condition of the Veteran river body is narrowing at a distance of 58 meters from the edge of the Martapura River with a width of up to 8 meters, and at a distance of 78 meters to 145 meters the width of the river body only reaches 3 meters. The shallowest point reaches (-) 0.074 meters at the mouth of the Veteran River, and the deepest point reaches (-) 13,311 meters in the Martapura River area. The basic condition of the cross section of the Veteran River estuary shows a relatively flat slope level. This shows a poor natural drainage system, where conditions like this can affect the volume of water flow in the Veteran River